Christ, the spirit, and human transformation in Gregory of Nyssa's in Canticum canticorum - Abecina, Alexander L. (Oxford studies in historical theology, 2024)
"It is generally agreed that virg. is Gregory of Nyssa's first written work, composed sometime in the early 370s. Recent scholarly interest in the text has tended to focus upon Gregory's alleged "ranking" of different forms of married and celibate life in relation to fourth century Christian asceticism. Rarely, however, has the overtly ascetical subject matter of the work been studied with regard to one of the most pressing doctrinal debates of the 370s and 380s, namely the dispute over the status of the Holy Spirit; a matter which the Cappadocian Fathers took up with great force against the Macedonians who denied the Spirit's essential unity with the Father and the Son. This chapter therefore investigates the role Gregory assigns to the Holy Spirit in the virgin's 'spiritual marriage' or union with Christ. I will show that Gregory stresses throughout the work that such union with Christ is in fact impossible for the naturally weak and fallen virgin unless it is actualised by the life-giving power of the Holy Spirit who shares in the very attributes of 'purity', 'incorruptibility' and 'virginity' that are proper to the Father and the Son. This he expounds with direct reference to baptismal theology. Thus, read in light of the debates with the Macedonians in the 370s and 380s, virg. can be understood to prescribe a form of ascetical life which rests upon the characteristically anti-Macedonian conviction that the Spirit, who is received at baptism, unites humanity to the Son and the Father because the Spirit is himself essentially united to the Son and the Father. This analysis of pneumatology in virg. is of central importance to my study of hom. in Cant: both works portray humanity's union with Christ under the metaphor of marriage. That Gregory construes this nuptial union in thoroughly pneumatological and hence baptismal terms in his earliest work serves to attune my focus upon resonant pneumatological and baptismal themes that shed light on his exegesis of the Song of Songs in his final written work"--